2012
DOI: 10.1016/j.micres.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and physiology of culturable bacteria associated with a coastal Antarctic ice core

Abstract: Microbiological studies of polar ice at different depths may provide important comparisons, as they preserve records of microbial cells and past climate. In this study, we examined bacterial abundance, diversity and glaciochemical composition from three depths of an ice core from coastal Dronning Maud Land, East Antarctica. Higher bacterial abundance corresponded with high in situ sea-salt Na(+) and dust concentration, suggesting that bacteria might have been transported and deposited into ice along with dust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 54 publications
5
23
0
Order By: Relevance
“…In the present study, isolates were producing extracellular enzymes such as esterase, protease, urease, amylase, etc. Similar study was done by Antony et al (2012), showed that bacteria isolated from Antarctic ice core region are also producing cold adaptive enzymes. These extracellular or cold-adaptive enzymes can be an important source of new catalysts possessing useful enzymological characteristics, e.g., Candida antarctica produces lipase A and B.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the present study, isolates were producing extracellular enzymes such as esterase, protease, urease, amylase, etc. Similar study was done by Antony et al (2012), showed that bacteria isolated from Antarctic ice core region are also producing cold adaptive enzymes. These extracellular or cold-adaptive enzymes can be an important source of new catalysts possessing useful enzymological characteristics, e.g., Candida antarctica produces lipase A and B.…”
Section: Discussionsupporting
confidence: 77%
“…Isolates were screened for starch hydrolysis, in ABM containing 1% soluble starch (Antony et al, 2012). After the proper growth, the plates were flooded with Gram's iodine and appearance of clear zone around the colony was taken as positive result.…”
Section: Biochemical Characterizationmentioning
confidence: 99%
“…Recently, bacterial abundance, diversity and glaciochemical composition from three depths, corresponding to 1926 AD, 1989 AD and 1953 AD, from an ice core of coastal Dronning Maud Land, East Antarctica have been analyzed (Antony et al 2012). Further, 14 bacterial isolates belonging to the genera Methylobacterium, Brevundimonas, Paenibacillus, Bacillus and Micrococcus were reported by Antony et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Further, 14 bacterial isolates belonging to the genera Methylobacterium, Brevundimonas, Paenibacillus, Bacillus and Micrococcus were reported by Antony et al (2012). The deep-sea environments of the South Atlantic Ocean were studied for culturable bacteria by Castro da Silva et al (2013), who reported that g-Proteobacteria and Firmicutes were the most frequently cultured with Halomonas the most frequent genus among the strains.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also revealed that the tephra accreted during the Agung (1963) and Krakatau (1883) eruptions harbored microbial cells (both coocoid and rods), suggesting that volcanic ash particles could provide a significant micro-niche for microbes and nanobes in the accreted ice (Laluraj et al, 2009). Microbiological studies of polar ice at different depths of the above ice core also provided an important comparison, as they preserve records of microbial cells and past climate conditions (Antony et al, 2012). The bacteria identified from the different depth of the ice core might have been transported and deposited into ice along with dust particles and marine aerosols.…”
Section: Palaeo-environmental Variability During the Past Five Centuriesmentioning
confidence: 99%